Radiation response of cancer stem-like cells from established human cell lines after sorting for surface markers. - Al-Assar, O; Muschel, R; Mantoni, T; Mckenna, W; Brunner, T (2009)
PURPOSE: A subpopulation of cancer stem-like cells (CSLC) is hypothesized to exist in different cancer cell lines and to mediate radioresistance in solid tumors. METHODS AND MATERIALS: Cells were stained for CSLC markers and sorted (fluorescence-activated cell sorter/magnetic beads) to compare foci and radiosensitivity of phosphorylated histone H2AX at Ser 139 (gamma-H2AX) in sorted vs. unsorted populations in eight cell lines from different organs. CSLC properties were examined using anchorage-independent growth and levels of activated Notch1. Validation consisted of testing tumorigenicity and postirradiation enrichment of CSLC in xenograft tumors. RESULTS: The quantity of CSLC was generally in good agreement with primary tumors. CSLC from MDA-MB-231 (breast) and Panc-1 and PSN-1 (both pancreatic) cells had fewer residual gamma-H2AX foci than unsorted cells, pointing to radioresistance of CSLC. However, only MDA-MB-231 CSLC were more radioresistant than unsorted cells. Furthermore, MDA-MB-231 CSLC showed enhanced anchorage-independent growth and overexpression of activated Notch1 protein. The expression of cancer stem cell surface markers in the MDA-MB-231 xenograft model was increased after exposure to fractionated radiation. In contrast to PSN-1 cells, a growth advantage for MDA-MB-231 CSLC xenograft tumors was found compared to tumors arising from unsorted cells. CONCLUSIONS: CSLC subpopulations showed no general radioresistant phenotype, despite the quantities of CSLC subpopulations shown to correspond relatively well in other reports. Likewise, CSLC characteristics were found in some but not all of the tested cell lines. The reported problems in testing for CSLC in cell lines may be overcome by additional techniques, beyond sorting for markers.